An assessment of the role of nanosilica in thermal/thermo‐oxidative degradation mechanism of poly(lactic acid)/polybutylene adipate terephthalate blend nanocomposites - Khonakdar, Hanieh; Khasraghi, Samaneh Salkhi; Yazdanbakhsh, Amir Hossein; Mousavi, Seyed Rasoul; Ahmadi, Shervin; Arabi, Hasan; Nobre, Marcos A. L. [UNESP]; Khonakdar, Hossein Ali (Wiley, 2024)
Abstract As a packaging materials candidate, based on a polylactic acid/ polybutylene adipate terephthalate (PLA/PBAT) blends (90/10 and 75/25 wt/wt) containing 1, 3, and 5 phr hydrophilic (HPL) and hydrophobic (HPB) nanosilica (NS) particles in the presence of a multifunctional epoxide compatibilizer were prepared by melt mixing, in a twin‐screw extruder. Scanning electron microscopic studies confirmed a matrix‐droplet morphology with finer dispersed domains at higher NS content. Energy dispersive spectroscopy mapping also indicated uniform dispersion of NS in blends, with some agglomerates at higher content of nanoparticles. Moreover, transmission electron microscope was applied to study the impact of nanofillers' localization on the systems' morphology. It was observed that NS particles localized at the PLA‐PBAT interface. In addition, thermogravimetric analysis (TGA) was used to investigate thermal stability and thermal degradation kinetics. Data indicates that hydrophobic NS improved thermal stability. The activation energy of degradation was calculated using several techniques of data modeling, including Friedman, Flynn‐Ozawa‐Wall, and Kissinger‐Akahira‐Sunose models. Among blend nanocomposites, 75/25 blend containing 5 phr HPB NS had the maximum degradation activation energy, suggesting that this sample had the most resistance to heat degradation. The intensity of the TGA/FTIR peaks of the evolved products was found to be correlated with the activation energy. The Criado's technique was also used to investigate the changes in the thermal degradation mechanism.